Advertising without gender stereotypes – can you do it? - Araújo, Simone (2014)
This article aims to discuss the continued use of gender stereotypes in television advertising. That because the male and female images have always been part of the history of advertising, however, one realizes that these are not always presented in a positive way by the consuming public, thereby causing a perpetuation of negative stereotypes in society. Therefore, the struggle for the deconstruction of stereotypes in advertising leads us to ask: Can the creative process to function without the use of stereotypes? This is what this article seeks to answer, given that, over the years, advertising has become the "fairy godmother" of reality, presenting an almost unreal world through beautiful ads that turn "in the ugly beautiful" and is constantly launching advertising messages with their models and stereotypes considered "perfect" by influencing consumers to buy products and ideas. Thus, this article shows significant examples of advertisements that seek to promote a more egalitarian society, and how some groups in society are aware of the abusive use of stereotypical advertising, for example, the Culture Jamming. Despite gender stereotypes are considered unavoidable due to its strong cultural presence and to its rebound effect, the article reflects on the possibility of replacing the elements of the positive negative content, thus promoting a more conscious advertising to consumers.